PENGEMBANGAN MODEL INDUKTIF DALAM PEMBELAJARAN APRESIASI PUISI - Warsiman . (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
This research is conducted to improve the students‟ ability in appreciating poetry through the use of Inductive Model. This study applies Research and Development  method  which  has been  modified,  and  the  result  of  the  study is analyzed descriptively.  The result of the study reveals that the use  of Inductive Model is able to improve the students‟ ability in appreciating poetry by concerning eight instructional steps. The numerical improvement can be seen from the students‟ average scores in every treatment. On the first treatment, the students‟ average score is 60.9, the second treatment is 62.4 and on the third treatment is 65.3. Based on the criteria  of success,  the  students‟  average  scores seem to increase  from the  first treatment until the third treatment, from fair level into very good level. The first treatment  shows  an  increase  from  fair  level  into  excellent  level.  The  second treatment shows an increase from good to very good. Finally, the third treatment shows an increase from very good to excellent level